2022
DOI: 10.1021/acs.joc.2c01689
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Tandem Difluoromethylation/Cyclization of Alkenyl Aldehydes toward CF2H-Substituted Chroman-4-one Derivatives

Abstract: An efficient and facile visible-light-mediated tandem difluoromethylation/cyclization of alkenyl aldehydes, with easily accessible and air-stable [Ph3PCF2H]+Br– as the difluoromethylation reagent, has been established. A range of CF2H-substituted chroman-4-one skeletons and their derivatives, such as 2,3-dihydroquinolin-4­(1H)-ones, chroman, 3,4-dihydronaphthalen-1­(2H)-one, 2,3-dihydrobenzofuran, and 2,3-dihydro-1H-inden-1-one, are efficiently produced in moderate to good yields with excellent chemoselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…In 2022, Yang and coworkers showcased the visible light-mediated synthesis of difluoromethyl chroman-4-one derivatives utilizing 5 and Ir(ppy) 3 . [70] With this protocol, the authors also demonstrated the synthesis of difluoromethylated 2,3-hydroquinolin-4(1H)-one, 3,4-dihydronapthalen-1(2H)-one, chroman, 2,3-dihydrobenzofuran, and 2,3-dihydro-1H-inden-1-one utilizing the reported conditions. Wu and coworkers detailed the synthesis of difluoromethylated quinazolinones also utilizing 5 and Ir-(ppy) 3 .…”
Section: Difluoromethylation Cyclization Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Yang and coworkers showcased the visible light-mediated synthesis of difluoromethyl chroman-4-one derivatives utilizing 5 and Ir(ppy) 3 . [70] With this protocol, the authors also demonstrated the synthesis of difluoromethylated 2,3-hydroquinolin-4(1H)-one, 3,4-dihydronapthalen-1(2H)-one, chroman, 2,3-dihydrobenzofuran, and 2,3-dihydro-1H-inden-1-one utilizing the reported conditions. Wu and coworkers detailed the synthesis of difluoromethylated quinazolinones also utilizing 5 and Ir-(ppy) 3 .…”
Section: Difluoromethylation Cyclization Reactionsmentioning
confidence: 99%
“…Triphenyldifluoromethylphosphonium bromide ( 5 ) has also been utilized in many difluoromethyl addition‐cyclization protocols (Scheme 18). In 2022, Yang and coworkers showcased the visible light‐mediated synthesis of difluoromethyl chroman‐4‐one derivatives utilizing 5 and Ir(ppy) 3 [70] . With this protocol, the authors also demonstrated the synthesis of difluoromethylated 2,3‐hydroquinolin‐4(1 H )‐one, 3,4‐dihydronapthalen‐1(2 H )‐one, chroman, 2,3‐dihydrobenzofuran, and 2,3‐dihydro‐1 H ‐inden‐1‐one utilizing the reported conditions.…”
Section: Difluoromethylation (Cf2h)mentioning
confidence: 99%
“…The bromides that can undergo ground-state transition under visible light are designed, which allows direct homolysis of C sp 3 –Br (BDE = 68 kcal mol −1 ) without a photosensitizer. Furthermore, as important scaffolds of natural products and biologically active molecules, chroman-4-one derivatives exhibit a broad range of biological effects, such as anti-inflammatory, 13 antibiotic, 14 anti-aging, 15 anti-HIV, 16 and especially anti-tumor activities. 17 Therefore, the chroman-4-one framework was determined as one of the target fragments for the cyclization strategy.…”
Section: Introductionmentioning
confidence: 99%
“…By means of developing new reagents, including BnSeCF 2 H, ClSeCF 2 H, TsSeCF 2 H, and BT-SeCF 2 H, the direct introduction of SeCF 2 H group has shown wide applications in modifying the organic molecules, but a multistep synthesis was required and a key precursor, BnSeCF 2 H, was obtained in low yields (10–36%). In the past few years, bench-stable and easily accessible difluoromethyltriphenylphosphonium salts have emerged as attractive tools for difluoromethylation reactions . In 2017, Studer described one example about radical difluoromethylation of benzylic selenol with [Ph 3 PCF 2 H]Br under UV irradiation .…”
Section: Introductionmentioning
confidence: 99%